A Fixed Point Results for Multivalued Mappings in Hausdorff Fuzzy $b$−Metric Spaces and Applications (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we are interested in proving a general fixed pointtheorem for multivalued mappings in fuzzy $b$−metric spaces. The results presented in this paper not only generalize the findings from [23], but also yieldadditional specific outcomes. We present an application to establish the existence of a solution to the integral equation, demonstrating the significance ofour result.
Keywords: Fuzyy metric space; fuzzy $b$−metric space; t-norm; fixed point; implicit relation.